The hydrazide/hydrazone click reaction as a biomolecule labeling strategy for M(CO)(3) (M = Re, (99m)Tc) radiopharmaceuticals() - Ganguly, Tanushree (2011)
Facile reactivity of hydrazides and aldehydes was explored as potential coupling partners for incorporation into M(CO)(3) (M = Re, (99m)Tc) based radiopharmaceuticals. Both ‘click, then chelate’ and ‘prelabel, then click’ synthetic routes produced identical products in high yields and lacked metal-hydrazide/-hydrazone interactions, highlighting the potential of this click strategy.